Spherical Aberration-Corrected Metalens for Polarization Multiplexed Imaging - Shaodong Zhou (MDPI AG, 2021)
We present a terahertz spherical aberration-corrected metalens that uses the dynamic phase to achieve polarization multiplexed imaging. The designed metalens has polarization–dependent imaging efficiencies and polarization extinction ratios that exceed 50% and 10:1, respectively. Furthermore, opposite gradient phases can be applied to orthogonal polarizations to shift the imaging of the two polarized sources in the longitudinal and transverse directions. Indeed, we find that the metalens has a smaller depth-of-focus than a traditional metalens when imaging point sources with limited objective lengths. These results provide a new approach for achieving multifunctional beam steering, tomographic imaging and chiroptical detection.